Implementation of Operational Risk Management in Teller Units at Bank BCA KCU X - Pikatan, Ira Rakai; Sunaryo, Tarsicius; Mangani, Ktut Silvanita (CV. Publikasi Indonesia, 2024)
This research aims to determine how to implement operational risk management of teller units at PT Bank Central Asia KCU X in East Jakarta. Bank operational risks continue to evolve and require good risk management to reduce the emergence of other risks. The type of research used in this study is a quantitative method used to collect data and measure risk with the formula R = P X D. In collecting data, there are several methods used by the author, namely using participatory observation, interviews, document studies and also questionnaires involving tellers in BCA KCU X. The application of operational risk management takes place starting from the business process of the teller unit which starts from morning to evening. The business process starts with preparing the teller area, then the call to the queue for customers to transact to the end-of-day process, namely teller balancing and checking teller activity reports. The study results show that BCA has implemented operational risk management in accordance with Bank Indonesia regulations and has mitigation measures in place for the risks that occur. The benefit of this research is that it will increase insight for similar agencies in implementing reliable operational risks.